(untitled) (Revista Contexto & Educação, 2026)
This study investigated the perceptions of undergraduate Physical Education students in Minas Gerais regarding their formative experiences in courses focused on inclusive education. It is a qualitative research, based on an online questionnaire answered by 41 students. The data analysis, guided by Bardin’s (2011) content analysis technique, revealed that students recognize the relevance of inclusive education subjects, although they point out limitations related to course workload and the depth of content. Practical experiences, such as internships and participation in Pedagogical Residency programs, were considered essential for connecting theory and practice, contributing to greater confidence in professional performance. The findings also highlighted students’ interest in continuing education, as they seek additional courses to deepen their knowledge of inclusion. It is concluded that, despite curricular progress, there is still a need to strengthen both initial and ongoing teacher education with a focus on inclusion, in order to promote more critical, sensitive, and socially engaged pedagogical practices. Expanding and improving these training opportunities may help develop professionals better prepared to act ethically, reflectively, and inclusively in diverse educational settings.